Strategi Badan Amil Zakat Nasional (BAZNAS) dalam Meningkatkan Jumlah Muzakki di Kota Bekasi - Imam Setiawan; Muhammad Nur Kholish AR; Sobirin Sobirin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The increasing number of zakat payers (muzakki) has not only elevated the zakat funds collected but also fostered greater public awareness and community participation in advancing social welfare. Data from Baznas Bekasi City show consistent growth in the number of muzakki: 153,158 in 2020, 205,770 in 2021, 276,743 in 2022, and 286,961 in 2023. This study explores the strategies employed by Baznas Bekasi City to increase the number of muzakki and addresses challenges encountered during implementation. Using a descriptive qualitative approach, the research analyzes Baznas Bekasi City’s efforts through data gathered via observation, interviews, and documentation. The findings reveal that strategies are based on SWOT analysis, emphasizing strengths such as official institutional status, a broad network, diverse programs, and a commitment to transparency. Opportunities include growing religious awareness, collaboration with organizations, technological innovation, and active public engagement through events and campaigns. These strategies have collectively driven the steady increase in the number of muzakki in Bekasi City.